2020
DOI: 10.1038/s41598-020-68825-2
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar transcranial direct current stimulation for learning a novel split-belt treadmill task: a randomised controlled trial

Abstract: This study aimed to examine the effect of repeated anodal cerebellar transcranial direct current stimulation (ctDcS) on learning a split-belt treadmill task. thirty healthy individuals randomly received three consecutive sessions of active or sham anodal ctDcS during split-belt treadmill training. Motor performance and strides to steady-state performance were evaluated before (baseline), during (adaptation), and after (de-adaptation) the intervention. the outcomes were measured one week later to assess absolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…For example, Galea et al [46] showed that anodal tDCS over the right cerebellum led to faster adaptation to a visuomotor rotation as evident by rapid reduction of movement errors compared to sham or to anodal tDCS to left M1. Later studies have replicated this finding with the same task [47,48], in older subjects [49], using force field adaptation [50] as well as in other forms of motor skill learning that require adaptation to a visuomotor manipulation [50][51][52][53]. However, recent attempts to replicate the positive effect of cerebellar tDCS on visuomotor adaptation in large groups of subjects were not successful [54][55][56].…”
Section: The Effect Of Non-invasive Stimulation Of the Cerebellum On Visuomotor Adaptationmentioning
confidence: 99%
“…For example, Galea et al [46] showed that anodal tDCS over the right cerebellum led to faster adaptation to a visuomotor rotation as evident by rapid reduction of movement errors compared to sham or to anodal tDCS to left M1. Later studies have replicated this finding with the same task [47,48], in older subjects [49], using force field adaptation [50] as well as in other forms of motor skill learning that require adaptation to a visuomotor manipulation [50][51][52][53]. However, recent attempts to replicate the positive effect of cerebellar tDCS on visuomotor adaptation in large groups of subjects were not successful [54][55][56].…”
Section: The Effect Of Non-invasive Stimulation Of the Cerebellum On Visuomotor Adaptationmentioning
confidence: 99%
“…The position of reflective markers was captured via nine-cameras at a frame rate of 200 Hz. The data were recorded during the last minute of the baseline phase and throughout the adaptation and the de-adaptation phase [ 61 ]. A MATLAB-based implementation of the Detection and Correction Algorithm (DACA) was utilised for determining the gait events: heel-strikes and toe-offs for each foot [ 62 ].…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Therefore, we cannot exclude that with only one tDCS session, the effects may have been minimal, where multiple sessions could have allowed for larger and more long-lasting effects of stimulation to manifest. However, a very recent study has evaluated the effects of three consecutive sessions of anodal cerebellar tDCS on motor learning measured during adaptation to a SBT task and found no significant effect compared to sham stimulation in a healthy population (Kumari et al, 2020). This result speaks against the potential benefit of multiple tDCS sessions on motor adaptation and consolidation.…”
Section: Limitations and Future Directionsmentioning
confidence: 98%